Manajemen Pelayanan Bidang Pendidikan sebagai Strategi dalam Menjaring Peserta Didik Baru di SMPN 3 Pagerwojo Kabupaten Tulungagung - Nurhajati, Nunun (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2022)
Education currently does not only focus on the context of the population or quantitative dimensions, but also on the qualitative dimensions or quality of education so that both processes and products are sought to produce human resources who are able to accept future challenges. Circumstances like this make there is competition in educational institutions to attract new, qualified students. To get a real picture of the management of education services in order to attract new students at SMPN 3 Pagerwojo, the data was taken by observing directly on the object of research as well as interviews with school leaders, teachers and the admissions committee of new students at SMPN 3 Pagerwojo. This was carried out in order to find out the education service management strategy that was carried out to attract new students at SMPN 3 Pagerwojo. Based on the results of the research, it can be concluded that SMPN 3 Pagerwojo in increasing the number of new students is to create programs so that student achievement can increase both academically and non-academicly, dividing into regular and superior classes, increasing achievement in non-academic fields. one in the field of musical and reog kendang. The most important strategy is to maximize the performance of the new student admissions committee.